Design and Realization of CAN Bus Interface for ARM Card - 聂火勇; 钟思琦 (机车电传动)
This paper described the characteristics of Samsung Corporation 32-bit ARM9 microprocessor core S3C2440 and Philips’s CAN controller SJA1000. According to time sequence requirements, the interface circuit between CPU and CAN controller had been realized by using programmable logic chips based on CPLD. The drive method had also been achieved under Linux. This paper provided the basic idea of connection conversion between non-multiplexed bus and time-multiplexed bus.